2010
DOI: 10.1007/s10439-010-0202-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Particle Residence Time in Abdominal Aortic Aneurysms Using Magnetic Resonance Imaging and Computational Fluid Dynamics

Abstract: Hemodynamic conditions are hypothesized to affect the initiation, growth, and rupture of abdominal aortic aneurysms (AAAs), a vascular disease characterized by progressive wall degradation and enlargement of the abdominal aorta. This study aims to use magnetic resonance imaging (MRI) and computational fluid dynamics (CFD) to quantify flow stagnation and recirculation in eight AAAs by computing particle residence time (PRT). Specifically, we used gadolinium-enhanced MR angiography to obtain images of the vessel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 42 publications
0
57
3
Order By: Relevance
“…It has been suggested that larger aneurysms are associated with increased convection flow, which, in the context of an aorta with normally very fast-flowing blood, leads to local pockets of reduced flow and shear stress. 31,32 This reduced flow, in combination with the propensity of patients with large aneurysms to form denser clots that are slower to lyse, could significantly increase the prothrombotic burden in the aneurysmal aorta. Furthermore, it is possible that a more densely packed clot may trap and accumulate a greater number of polymorphonuclear leukocytes, which in turn release biologically active proteases, causing AAA dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that larger aneurysms are associated with increased convection flow, which, in the context of an aorta with normally very fast-flowing blood, leads to local pockets of reduced flow and shear stress. 31,32 This reduced flow, in combination with the propensity of patients with large aneurysms to form denser clots that are slower to lyse, could significantly increase the prothrombotic burden in the aneurysmal aorta. Furthermore, it is possible that a more densely packed clot may trap and accumulate a greater number of polymorphonuclear leukocytes, which in turn release biologically active proteases, causing AAA dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…One might find this analogous to the normalization of residence time or exposure time by the volume in discrete methods. 13,14,16 Considering the schematic shown in Figure 4 and Eqs. (9), (10), (16) and setting n = u u gives…”
Section: Point-wise Rtmentioning
confidence: 99%
“…To obtain a measure of RT in a region of interest, most prior studies have proposed a discrete formulation in which particles are released in the flow and their locations are traced over time. [13][14][15][16][17] RT is then calculated based on the time each individual particle spends in the region of interest. RT results obtained from these approaches depend on the number of particles used, often requiring a large number of particles to obtain a smooth spatial distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Degradation of the aortic wall, inflammation with immune responses, and biochemical wall stress are mechanisms that promote AAA initiation, influenced by molecular genetics (1). After the irreversible process of aneurysm formation, the dilated vessel creates an environment with complex blood flow and wall shear stress distribution (4,5,9,14,22,37,38), which is thought to perpetuate aneurysm progression.The presence of intraluminal thrombus (ILT) complicates AAA growth. ILT is fibrin structure compound of platelets, blood cells, blood proteins, and cellular debris (20).…”
mentioning
confidence: 99%